A guideline to enforce privacy and data protection regulation in Indonesia - Lubis, Muharman; Kartiwi, Mira; Zulhuda, Sonny (South East Asia Journal of Business Economics and Law, 2013)
Indonesia has enacted the first cyberlaw, UU ITE 11/2008 as legal certainty and foothold to support transaction of electronic commerce in the Internet, within the boundaries of Indonesia. Generally, the regulation can be divided into two parts, the rule about concept of information, contract, certification and prohibition of illegal practice in terms of e-commerce through statement of remedies. In article 26 verse 1; it stated about the use of every information should be based on the user’s consent. Unfortunately, the nature of UU ITE is still common and basic as fundamental law to set standard in fulfilling cyber requirement. Therefore, the primary component for electronic commerce to run smoothly resides on process of collecting the data as input to the database derived from customer submission or transaction logs. However, no clear and concrete statement in the first Indonesia cyberlaw to accommodate with this matter whereas data is the critical factor determining the successes and set inter-relationship between party. This paper will present guideline in applying privacy and data protection regulation in Indonesia, specifically in terms of commercial and administrative purpose.